Pengaruh Temperatur Kalsinasi Terhadap Kapasitas Ion Katalis Asam Heterogen Berbasis Silika dan Aplikasinya pada Sintesis Metil Oleat: The Effect of Calcination Temperature on the Ion Capacity of Heterogeneous Silica-Based Acid Catalysts and Its Application in the Synthesis of Methyl Oleate - Joko Suryadi; Nanda Nabila; Syafa Neiska Bayhaqi; Eko Andrijanto (KOVALEN: Jurnal Riset Kimia, 2023)
Sulfated silica catalyst is a solid acid catalyst which in its application is used to accelerate esterification reactions. The purpose of this study was to determine the effect of calcination temperature and increasing the amount of catalyst on the effectiveness of silica as a catalyst in the formation of methyl oleate through esterification reactions. The synthesis of sulfuric acid catalyst from rice husk ash went through several stages, including preparation of raw material for rice husk ash, production of silica using the sol-gel method, manufacture of silica-based acid catalysts and characterization of the sulfated silica catalyst. The acid catalyst was prepared using impregnation method with sulfuric acid and calcined at various temperatures of 500, 600, 700 and 800oC. The characterization of the acid catalyst formed includes ionic capacity, catalyst performance in the esterification reaction, and the determination of the bond characteristic functional groups using FTIR. The results of ion capacity analysis showed that the highest acidity value was found in the sulfated silica catalyst calcined at 600oC of 0.372 mmol/gram. Testing the performance of the catalyst in the esterification reaction with a ratio of 4:1 (methanol:oleic acid) obtained an ester conversion of 38.89% using a catalyst of 30% of the amount of oleic acid. Identification results using FTIR show that sulfate ions have chemically interacted with silica at around 1103.28 cm-1